ONLINE-BASED MARKETING MANAGEMENT IMPLEMENTATION (Empirical Study of MSMEs in the Furniture Sector in Tasikmalaya) - Rinandiyana, Lucky Radi; Badriatin, Tine (EAJ (Economic and Accounting Journal), 2020)
The marketing problem is one of the problems that often arises by MSME business people. Where most MSME business people still rely on the marketing process by using old methods to introduce their business products while the recent economic growth is growing very rapidly, plus the support of advancing technology indirectly encourages furniture and furniture entrepreneurs to increase production. the lack of knowledge of MSME practitioners in using existing technology as promotional media certainly becomes an obstacle in the marketing process of MSME furniture production. Most of the SMEs in Jln Tamansari Gobras, Tasikmalaya City, only 70% understand and apply the concept of online-based marketing in introducing the results of furniture production, where MSMEs still use banners or banners for media promotion and sales management still using manual methods, so that sales reach very limited. The purpose of this study was to determine the implementation of online-based marketing management concepts in the development of online-based marketing management business and the role of online-based marketing implementation in increasing sales turnover in MSME furniture and furniture production in the village of Tamansari Gobras in Tasikmalaya City. This research uses a descriptive method. The results showed that Babakan Muncang Tamansari Gobras MSMEs, the City of Tasikmalaya had to increase their knowledge to do online marketing to increase their income without having to spend a lot of funds as capital which experienced a 3.8% decline in sales then to expand their market share by selling online. SMEs in the village of Babakan Muncang Tamansari Gobras in the City of Tasikmalaya are expected to implement online marketing management to bring reservations without having to come directly to the place of business.Keywords: Marketing,  Online Sales